Prolonged SARS-CoV-2 shedding and mild course of COVID-19 in a patient after recent heart transplantation - Decker, Annegrit (Am J Transplant, 2020)
In the coronavirus disease 2019 (COVID-19) pandemic, organ transplant recipients are considered to be at high risk for an unfavorable outcome. However, in particular the role of immunosuppression in patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remains undetermined. Here, we present a 62-year-old male COVID-19 patient with recent heart transplantation who developed only mild symptoms, but had prolonged virus shedding, and summarize the available data on COVID-19 in cardiac allograft recipients. Initially the patient presented with a transient episode of fever and sore throat but no other symptoms, in particular no cough or dyspnea at rest. After diagnosis, immunosuppression was continued unchanged. On day 7, his temperature increased again with concurrent mild rise of C-reactive protein, IL-6, and pro-B-type natriuretic peptide levels. Hydroxychloroquine was started and continued for 7 days. While the patient no longer had clinical symptoms 20 days after initial presentation, virus culture of throat swabs on days 18 and 21 confirmed active virus replication and SARS-CoV-2 PCR remained positive on day 35 with copy numbers similar to the onset of infection. In conclusion, the immunosuppression regimen in transplant recipients with mild COVID-19-associated symptoms may be continued unchanged. However, it may contribute to delayed virus polymerase chain reaction conversion and thus possible prolonged infectivity.